Technical Assistance and Renovation Planning, Petompon Sub-district Hall, Gajahmungkur District, Semarang City - Eko Budi Santoso; Diharto; Wiwit Setyowati; Ardiyan Adhi Wibowo; Fisa Savanti; Fahrudin Fahrudin; Vicky Rosyid Hidayat; Salwa Nur Fadilah; Sintia Putri Maulita (Jurnal Abdimas, 2024)
This community service activity is carried out by identifying and inventorying problems with sub-district officials, discussing alternative solutions to problem-solving until the solution is selected, and then making pre-designed drawings, which are then carried out by presenting the results and submitting planning documents. After the pre-design drawings have been discussed and mutually agreed upon, a final renovation design and the required budget plan are created. The results of this Community Service are a Renovation Planning Document for the Petompon Sub-district Hall, which will guide government institutions in building and developing the building.